Management of Dakwah Pattern Method Development in School Students - Erick Yusuf; Sofyan Sauri; Ahmad Sukandar (UIN Sunan Gunung Djati Bandung, 2019)
This research is motivated by a decline in morals which is increasingly widespread in this millennial era. The development of information technology that has entered the industrial revolution 4.0 has a huge impact on the behavior and culture that develops in society. Apart from positive things, of course the negative impacts are due to the very openness of information that can be accessed by all people, including children. Among them are the many hoaxes and trash information as well as misleading information. There needs to be a self-built filtration system to sort them out. One of them is the education system in schools. This phenomenon often becomes an apology for some people to give their scathing criticism of educational institutions. Based on the results of the study, it was found that the IHAQI Boarding School Creative Junior High School had good management in implementing the guidance method of the dakwah pattern. The planning of using the dakwah pattern as a learning method carried out by educators at the IHAQI Boarding School Creative Junior High School has been carefully planned. As for the implementation of the use of the da'wah method at the IHAQI Boarding School Creative Junior High School, it is felt that it has been carried out effectively. So that the evaluation of the use of da'wah patterns in learning at the IHAQI Boarding School Creative Junior High School is enough to give a very deep impression to all students to inherit Islamic values. It's just that there are several obstacles and constraints that occur at this Creative Junior Boarding School which is centered on the realm of communication.